Educational values in the Quran: Surat Luqman and AL- Hujurat model - دلال كاظم عبيد (College of Education for Women, 2019)
The paper has been summarized into the following: Chapter one: the researcher deals with the problem of the paper, the most important points and the terminology. Chapter two: the researcher deals Surat Luqman from the Aya 12-19 , (the demonstration, the explanations, the values ). In chapter three the researcher deals with Surat AL-Hujurat from Aya 6-12, (the demonstration, the explanations, the values ). Chapter four include (the educational properties for individual and society, the educational applications, and the most important indicators in the texts). Chapter five include the results , the conclusions and the recommendations. One of the basic results that the Quran is a complete educational curriculum, and the texts of Surat Luqman and Surat AL-Hujurat includes global connected educational values, and both implies the same results. The conclusions are: the ways and methods of teaching the Quran is not worthy and the holy Quran do not used as educational curriculum. In the recommendations: it is better to change the ways and the methods of teaching the Quran and take technical teaching methods, make the holy Quran educational curriculum in all stages of learning and educations.